Capturing what remains: A commentary on Kidd and Garcia (2022). Issue 6 (December 2022) - Slobin, Dan
Kidd and Garcia remind us of the urgency of gathering comparable child language data across languages and cultures. They provide useful guidelines, and more are suggested here. Languages used for comparative analysis should be picked with regard to precise typological contrasts, pinpointing structures that promise to reveal processes of acquisition. Our knowledge gap may not be as severe as it seems to the authors; nevertheless, we are faced with daunting tasks of collecting data and preparing them for detailed analysis.